Metrology Feasibility Study in Support of the National Direct-Drive Program. (17th February 2018) - Huang, H.; Engelhorn, K.; Sequoia, K.; Greenwood, A.; Sweet, W.; Carlson, L.; Elsner, F.; Farrell, M.
Abstract: The 100-Gbar Laser Direct Drive program calls for ablator capsules with no defects larger than 0.5 μm in lateral dimension and fewer than ten defects with lateral dimensions between 0.1 and 0.5 μm. Compared to laser indirect drive capsules, this represents > 10× reduction of defect length scale and >500× reduction in defect number density. This presents major challenges to both fabrication and metrology. In this paper, we will discuss the proof-of-principle work conducted at General Atomics to identify metrology techniques suitable for 100-Gbar target characterization. We present a detailed study of dark-field imaging, laser scatterometry, and environmental scanning electron microscopey. We identify dark-field imaging as the best approach for meeting the 100-Gbar metrology needs.